Strategi Penguatan Manajemen UMKM Pesisir Cilacap melalui Pelatihan dan Pendampingan Berbasis Kebutuhan Lokal: Strategi Penguatan Manajemen UMKM Pesisir Cilacap melalui Pelatihan dan Pendampingan Berbasis Kebutuhan Lokal - hastuti, Hetydwi; Alfarisi Akbar Efendi, Alfarisi Akbar Efendi; Sasongko Adi Priyanto, Sasongko Adi Priyanto (Papanda Publisher, 2025)
This study addresses the urgent need to strengthen the management capacity of micro, small, and medium enterprises (MSMEs) in the coastal region of Cilacap through training and mentoring based on local needs. The research aims to formulate and evaluate an effective model that enhances managerial skills, digital marketing competency, and legal compliance in MSMEs. A qualitative case study approach was employed, involving in-depth interviews and observations with 30 MSME actors and 20 mentoring recipients located in Cilacap. Data were collected using semi-structured interview guides, direct field observations, and documentation from training activities. Results indicate significant improvements in financial management practices, marketing outreach via digital platforms, and ease in obtaining legal certifications such as PIRT and halal certification. The mentoring process played a crucial role as a mediator that enhanced the practical application of training content, resulting in sustainable behavioral changes that improve business competitiveness. This study proposes integrating continuous mentoring with participatory and contextualized training to optimize MSME empowerment in coastal areas. Future research is expected to explore the scale-up of the model using remote communication technologies and its impact over longer terms.